A3_7 Two mirrors and infinity - Karazhov, Dennis; Ryan, Liam; Booth, Tim (Physics Special Topics, 2011)
We work through a scenario of an observation of multiple images when two parallel mirrors are facing each other, with an omnidirectional light source situated between them. We find that a typical conventional light bulb as a source shall initiate approximately 83 images perceivable by human eye.